Conversion Disorder Presenting with Unilateral Photophobia and Vision Loss. - Chang, Amy; Bateman, Jennifer; Capó-Aponte, José E. (Optometry & Visual Performance, 2015)
Background: Conversion disorder is a rare condition and consequently is often misdiagnosed. Patients suffer from neurological symptoms in the absence of an organic cause. Symptoms arise in response to a stressful or traumatic situation affecting the patient's mental health which converts to a physical problem. Although it is a psychiatric condition, conversion disorder typically affects motor or sensory systems. Case Report: This report describes a 38-year-old military female presenting with unilateral photophobia and vision loss resulting from a traumatic combat experience. The diagnosis of conversion disorder was made after ruling out organic causes (e.g., ocular, visual, neurological) and extensive history and health record review. Conclusion: Conversion disorder should be considered in patients with a sensory visual deficit in the absence of an organic cause. A thorough review of the patient's psychological history is important when dealing with unexplained sensory deficits.